Students’ Knowledge and Attitude toward Genetic Engineering - Purwanti Pratiwi Purbosari; Parni Astuti (Postgraduate, University of Mataram, 2023)
Students are the people who will be consumers, producers, and policymakers of genetic engineering application products in the future. This paper reviewed research exploring the students' knowledge and attitude toward genetic engineering through a narrative literature review of articles published between 2012 and 2022. After applying criteria of inclusion, exclusion, and thematic belonging in google scholar databases, the sample was constituted of 20 studies. The results showed that most secondary school students needed more knowledge of genetic engineering, even in countries that produce genetically modified organisms through genetic engineering nationally. Most studies also revealed that most students expressed a negative attitude toward genetic engineering and its products. Besides that, students with a positive attitude toward genetic engineering often showed multiple attitudes, depending on which aspects they focus on.